Organization in Biology - Mossio, Matteo (History, Philosophy and Theory of the Life Sciences, 2024)
This open access book assesses the prospects of (re)adopting organization as a pivotal concept in biology. It shows how organization can nourish biological thinking and practice, by reconnecting with the idea of biology as the science of organized systems. The book provides a comprehensive state-of-the-art picture of the characterizations and uses of the concept of organization in both biological science and philosophy of biology. It also deals with a variety of themes - including evolution, organogenesis, heredity, cognition and ecology - with respect to which the concept of organization can guide the elaboration of original models and new experimental protocols. It will be of interest to biologists and scholars working in philosophy of science alike.